Uncertainty & plenitude : five contemporary poets - Stitt, Peter (University of Iowa Press, 1997)
Stitt's interest in these five poets is intellectual and aesthetic. As he states, "I chose these particular writers because their work continues to interest me deeply, both intellectually and formally, even after years of familiarity." He uses his understanding of the philosophical implications inherent in modern physics, as they apply to both content and form, as the basis for his close analysis. Stitt attends to the poet's writerly strategies so that we may discover in their poetry where "surface form" intersects and complements meaning and thus becomes, in John Berryman's terms, "deep form". He explains what these poets say and how they say it and what relationships lie between. He also shows how humor plays a part in some of their work.